Cognition and multiple sclerosis: a neuropsychological and MRI study - Thornton, Helena Barbara (Rhodes University, Faculty of Humanities, Department of Psychology, 1996)
Ten people with multiple sclerosis (MS) who felt they had cognitive difficulties because of their MS were investigated. This study had multiple aims. Firstly, to explore the subjective experience of cognitive deficits. Secondly, to assess whether or not there was objective evidence of cognitive difficulties on neuropsychological testing, and whether this was commensurate with a pattern of subcortical dementia. Thirdly, to determine whether their magnetic resonance imaging (MRI) scans replicated the patterns of atrophy frequently reported in MS patients with cognitive difficulties. And finally, to investigate the psychological well-being of the subjects. In depth neuropsychiatric interviews, psychiatric and psychological inventories, a comprehensive neuropsychological battery, and MRI investigations were done. The mean Full Scale Intelligence Quotient (FSIQ) fell within the superior range, at the 89th percentile. On tests of general intelligence, mental state examinations, there was little or no indication of cognitive deterioration. However, on sophisticated neuropsychological testing, there was convincing evidence of cognitive problems. Magnetic resonance imaging lesions were atypical of the reported research on cognitively compromised MS patients.
Keywords: Multiple sclerosis -- Magnetic resonance imaging; Cognitive neuroscience